Hubungan Sifat Optik terhadap Performa Kinerja Sel Surya DSSC Transparan Berbahan Dye DN-F01 sebagai Sensitizer - Agus Supriyanto; Ari Handono Ramelan; Mohd Khairul Bin Ahmad; Febrina Ramadhani; Diani Galih Saputri (Department of Physics, Sebelas Maret University, 2020)
Dye sensitized solar cell (DSSC) is the third generation of solar cells that currently developing by researchers to get the best performance. The selection of dye as a component of DSSC has a big influence in the light absorption process. In this study, DN-F01 organic dye was used as a sensitizer with various concentrations. The optical properties test was carried out on the DN-F01 dye solution by UV-Vis spectrophotometer (Shimadzu UV-1800) and the DSSC fabricated performance was tested by portable solar simulator (ORIEL Sol1A). From the results, the DN-F01 absorbance has ability to absorb light in the 300-500 nm wavelength range. The greatest efficiency value in this research is 2.44% obtained from the sample was immersed with the largest concentration of dye DN-F01 which has the smallest band gap energy of 2.38 eV.